High level of nickel tolerance and metal exclusion identified in silver maple (Acer saccharinum). Issue 9 (21st October 2017) - Nkongolo, K. K.; Narendrula-Kotha, R.; Kalubi, K.; Rainville, S.; Michael, P.
ABSTRACT: Nickel (Ni) and copper (Cu) are the most prevalent metals found in the Greater Sudbury Region ecosystems. The main objectives of this study are to (1) assess silver maple (Acer saccharinum ) tolerance to different doses of Ni and (2) determine the translocation pattern of metals in A. sacharinum . This study revealed that A. sacharinum is highly tolerant to high doses of NI (1600 and 9200 mg/kg). Growth chamber screening trials revealed that Ni is stored in roots and does not translocate to other plant parts. Analysis of samples from A. sacharinum growing for >30 years in soil contaminated with metals also showed that the levels of iron (Fe), manganese (Mn), Ni, and zinc (Zn) were significantly higher in roots compared with soils and aerial parts. On the other hand, the amount of Cu was higher in soil compared with roots and other plant parts. In fact, the bioaccumulation factors (BFs) were 0.29, 2.00, 3.6, 1.9, and 4.0 for Cu, Fe, Mn, Ni, and Zn, respectively. The translocation from roots to aerial parts showed an insignificant level of movement of Cu, Fe, and Ni. Hence, A. saccharinum is classified as excluder for Fe, Mn, Ni, and Zn, and avoider for Cu.